Spatial Analysis of Crime against Women in Bahadurgarh City: Understanding the Spatial Pattern of Crime against Women in Bahadurgarh City (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The problem of crime against women is not new. Women in Indian society have been victims of ill- treatment, humiliation, torture and exploitation for as long as written records of social organization and family life are available. These records are replete with incidents of abduction, rape, murder and torture of women. The main reason of that crime is the attitude of indifference and negligence which can be attributed to factors like lack of awareness of seriousness of the problem, general acceptance of man’s superiority over women because crime acts against women were not viewed as crime or deviant and the denial of crime by women themselves owing to their religious value and socio-cultural attitude. The present study comprises the Bahadurgarh City wards. In Bahadurgarh City police has 31 wards. The study based on secondary data sources. The data collected from the Bahadurgarh police station shows the spatial pattern of these crimes. There are eleven categories of crime which come under “crime against women”. However, data at ward level in Bahadurgarh city could be available only for seven categories, i.e. rape, kidnapping, molestation, dowry death, torture (i.e. cruelty by husband or his relatives), murder (except dowry death), and sexual harassment. Due to this reason, the maps are showing the spatial pattern of crime against women at ward level for these categories only. There were 523 cases reported under seven categories of “crime against women” between 2001 to 2014. The cases under rape, kidnapping, dowry death, molestation, importation of girls, torture and murder are 62, 40, 19, 21, 44, 337 and 0 respectively. To reduce these crimes,a ll appropriate measures should be taken to ensure to women, married or unmarried, equal rights with men in the field of political, economic and social life.